The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1086/685054
|View full text |Cite
|
Sign up to set email alerts
|

Unexplained Exertional Dyspnea Caused by Low Ventricular Filling Pressures: Results from Clinical Invasive Cardiopulmonary Exercise Testing

Abstract: To determine whether low ventricular filling pressures are a clinically relevant etiology of unexplained dyspnea on exertion, a database of 619 consecutive, clinically indicated invasive cardiopulmonary exercise tests (iCPETs) was reviewed to identify patients with low maximum aerobic capacity (V O 2 max) due to inadequate peak cardiac output (Qtmax) with normal biventricular ejection fractions and without pulmonary hypertension (impaired: n = 49, V O 2 max = 53% predicted [interquartile range (IQR): 47%-64%],… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 28 publications
0
51
1
1
Order By: Relevance
“…Finally, the relative syndrome-dependent inactivity among POTS patients might hypothetically lead to a reversal or gross disturbance in circadian patterns of GH release. However, deconditioning as an underlying pathophysiology of POTS and to possibly related syndromes such as chronic fatigue syndrome has not been supported by recent studies, and other mechanisms such as low ventricular filling have been proposed [34,35]. It remains to be demonstrated if physical training may reverse GH level abnormality.…”
Section: Growth Hormonementioning
confidence: 99%
“…Finally, the relative syndrome-dependent inactivity among POTS patients might hypothetically lead to a reversal or gross disturbance in circadian patterns of GH release. However, deconditioning as an underlying pathophysiology of POTS and to possibly related syndromes such as chronic fatigue syndrome has not been supported by recent studies, and other mechanisms such as low ventricular filling have been proposed [34,35]. It remains to be demonstrated if physical training may reverse GH level abnormality.…”
Section: Growth Hormonementioning
confidence: 99%
“…52 Many patients with HFpEF will have low LV filling pressures at rest requiring assessment with exercise. 37,38,53 iCPET is also required to confirm the diagnosis of EiPH. 54 Figure 3, left column, demonstrates the typical findings in an EiPH patient with normal resting hemodynamics but increased mPAP, PVR, V E/V CO 2, and reduced V O 2 max and V O 2 /HR.…”
Section: Discussionmentioning
confidence: 99%
“…However, a more recent study has shown that deconditioning is not the primary underlying mechanism for POTS. Oldham and colleagues 10 showed that exercise intolerance does not result from a lack of enough exercise, but from low ventricular filling pressures even during maximum effort.…”
Section: The Role Of Deconditioningmentioning
confidence: 99%